“No Country for Old Men”? The Question of George Moore’s Place in the Early Twentieth-Century Literature of Ireland - Jarząb-Napierała, Joanna (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The paper scrutinizes the literary output of George Moore with reference to the expectations of the new generation of Irish writers emerging at the beginning of the twentieth century. Although George Moore is considered to belong to the Anglo-Irish ascendancy writers, he began his writing career from dissociating himself from the literary achievements of his own social class. His infatuation with the ideals of the Gaelic League not only brought him back to Dublin, but also encouraged him to write short stories analogous to famous Ivan Turgenev’s The Sportsman’s Sketches. The idea of using a Russian writer as a role model went along with the Gaelic League advocating the reading of non-English European literature in search for inspiration. However the poet’s involvement in the public cause did not last long. His critical view on Ireland together with his uncompromising approach towards literature resulted in a final disillusionment with the movement. The paper focuses on this particular period of Moore’s life in order to show how this seemingly unfruitful cooperation became essential for the development of Irish literature in the twentieth century. The Untilled Field, though not translated into Irish, still marks the beginning of a new genre into Irish literature—a short story. More importantly, the collection served as a source of inspiration for Joyce’s Dubliners. These and other aspects of Moore’s literary life are supposed to draw attention to the complexity of the writer’s literary output and his underplayed role in the construction of the literary Irish identity.